Formulasi cookies sebagai makanan pendamping air susu ibu untuk balita gizi buruk - Estu F. Dewi, Yohanes Kristianto (Berita Kedokteran Masyarakat (BKM), 2006)
Background: Commercially available supplementary foods are very often not affordable particularly to the unfortunate sufferer of under nutrition families. Supplementary food should therefore be carefully formulated by involving locally available foods and feasible technology to increase its sustainability, Objective: This research was aimed to produce supplementary food in form of cookies by the use of tempe and red bean flour. Methods: The study was conducted using completely randomised design. Anova was performed to determine the effects of the formulation to the qualities of end product, Results: Showed that two pieces of the cookies (20gr) produced using tempe and red bean flour ratio of 10:30% were sufficient to provide 10% energy requirement of children aged 7 — 12 months. The protein and Fe contents of the cookies were higher than that of commercial cookies. The energy protein ratio of the cookies was well above the recommendation and this was also true for the protein score. In short, this study demonstrates that high quality supplementary food for undernourished children can be locally produced. Conclusion: Further work may be carried as an effort to decrease fat content of the cookies while increasing carbohydrate at the same time. Keywords: under nutrition, tempe, red bean, supplementary food